2015
DOI: 10.1038/pr.2015.252
|View full text |Cite
|
Sign up to set email alerts
|

Yinzhihuang attenuates ANIT-induced intrahepatic cholestasis in rats through upregulation of Mrp2 and Bsep expressions

Abstract: Background:The treatment of intrahepatic cholestasis has been limited, and development of an effective drug is needed. Clinical studies have shown that Yinzhihuang (YZH), a traditional Chinese decoction, enhances bilirubin clearance. The goal of this study was to determine the protective effect of YZH on experimental intrahepatic cholestasis in young rats and to explore its underlying molecular mechanisms. Methods: Intrahepatic cholestasis in rats was induced by α-naphthylisothiocyanate (ANIT) on days 1 and 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
3
9
1
Order By: Relevance
“…4 and 6). Interestingly, the results were contradictory to ANIT-reduced Mrp2 and Bsep expression reported in a recent study (Ou et al, 2016) as well as unchanged Bsep, Mrp2 and SHP expression reported in a previous study on FXR agonist GW4064 (Liu et al, 2003). In addition, bile duct ligation or lipopolysaccharide (LPS) treatment resulted in an IL-1β-mediated retinoic acid receptor alpha (RARα)/retinoid X receptor alpha (RXRα) downregulation, which in turn decreased Mrp2 transcription in rats (Denson et al, 2002;Takikawa, 2002).…”
Section: Discussioncontrasting
confidence: 99%
“…4 and 6). Interestingly, the results were contradictory to ANIT-reduced Mrp2 and Bsep expression reported in a recent study (Ou et al, 2016) as well as unchanged Bsep, Mrp2 and SHP expression reported in a previous study on FXR agonist GW4064 (Liu et al, 2003). In addition, bile duct ligation or lipopolysaccharide (LPS) treatment resulted in an IL-1β-mediated retinoic acid receptor alpha (RARα)/retinoid X receptor alpha (RXRα) downregulation, which in turn decreased Mrp2 transcription in rats (Denson et al, 2002;Takikawa, 2002).…”
Section: Discussioncontrasting
confidence: 99%
“…Alkaline phosphatase (ALP) is determined in the cells of the bile duct and is often employed to assess the reliability of the plasma membrane of the liver (Ou et al, 2016). The data recorded in the present study showed a significant increase of the serum ALP activity in cholestatic rats, which consonance with the findings of Lin et al (2012).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, treatment with Ech causes a general decrease in total bilirubin, direct bilirubin, and indirect bilirubin throughout, as compared to ANIT group. The recorded reductions may reflect the role of Ech in helping bilirubin clearance from circulation as recorded by Ou et al (2016). Histopathological examination of liver sections confirmed our biochemical findings.…”
Section: Discussionsupporting
confidence: 84%
“…Traditional medicines and natural products have been widely used to treat cholestasis for thousands of years [ 22 24 ]. Dried black bear’s bile was recommended in China for the treatment of jaundice during the Tang dynasty (618-907 A.D.), as documented in the Tang Materia Medica, the first state pharmacopoeia [ 25 ].…”
Section: Introductionmentioning
confidence: 99%